Impact of Bhakti and Sufi Mysticism on Social Harmony: Understanding Mystical Experiences and Practices - Salman Faris TC (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
This research article offers a comparative analysis of the Bhakti Movement in Hinduism and Sufi Mysticism in Islam, two profound spiritual movements that emerged in India and the Islamic world, respectively. Through an exploration of their historical backgrounds, philosophical foundations, practices, and impacts on society, this study aims to shed light on the similarities and differences between these influential religious movements. The research delves into the ways in which both the Bhakti Movement and Sufi Mysticism have fostered devotion, inclusivity, and a profound connection to the divine, while also recognizing their unique cultural contexts and expressions. The analysis seeks to provide a deeper understanding of the transformative power of religious devotion in diverse cultural and religious landscapes. The article also discusses the potential interconnections between Bhakti and Sufi thought, unveiling the possibility of cross-cultural influences that may have shaped the spiritual fabric of both traditions. The investigation will delve into the historical contexts that gave rise to the Bhakti Movement and Sufi Mysticism, their roles in promoting religious pluralism and interfaith dialogue, and the ways in which they have influenced the spiritual lives of their adherents.